Minat Beli Sebagai Variabel Intervening Pada Pengaruh Citra Merek Dan Promosi Terhadap Keputusan Pembelian Mascara Maybelline - Mely Susianawati; Andri Nurtantiono (JURNAL ILMIAH EDUNOMIKA, 2022)
The reason for this reasoning is to determine the impact of Brand Image and Promotion on Purchase Decisions with Purchase Intention as an intermediary variable. This strategy uses path analysis. The test used was 97 respondents. Collecting information by means of a questionnaire. It turns out that the variables of Brand Image and Promotion have an impact on Buying Interest at the same time. The Brand Image variable displays a noteworthy impact on Purchase Intention. The progress variable is partially unimportant for intentional purchases. The concurrent impact of Brand Image, Promotion, and Buying Interest factors have a synchronous impact on Purchase Decision. Partial Impact of Brand Image and Purchase Interest have an impact on Purchase Decision, while promotion is not affected by Purchase Decision. Keyword: Brand Image, Promotion, Purchase Interest, Purchase Decision